Infectious Etiologies of Stroke - Shulman, Julie G.; Cervantes-Arslanian, Anna M. (Seminars in Neurology, 2019)
Central nervous system (CNS) infections are a frequently underappreciated potential etiology of cerebrovascular disease. Highlighted in this review are a selection of infectious agents that lead to cerebrovascular complications through various mechanisms including multifocal vasculopathy, focal infiltrative vasculitis and vasospasm, and direct vessel wall invasion and thrombus formation. Diagnosis of stroke due to underlying CNS infection requires a high index of clinical suspicion and careful consideration of neuroimaging, serum, and cerebrospinal fluid studies in addition to a detailed history and neurologic examination. Prompt and targeted treatment is essential in these conditions, which frequently herald a poor prognosis. Specifically, cerebrovascular complications associated with varicella zoster virus, syphilis, tuberculosis, aspergillosis, and acute bacterial meningitis are addressed here in detail.
Keywords: stroke; infection; vasculitis; vasculopathy